AHP기법을 통한 성과관리전략 수립방안 - 황의식 (한국농촌경제연구원, 2007)
The objective of this study is to develop the performance evaluation strategies for the agricultural policy with AHP analysis. This study includes goals and management strategies to affect the major elements of financial factors, institutional factors, environmental factors. The AHP is a structured technique for dealing with complex decisions and provides a comprehensive and rational framework for structuring a problem, for relating those elements to overall goals, and for evaluating alternative solutions. It is used throughout the world in a wide variety of decision making filed, in fields such as government, business, industry, healthcare, and education. With 4 goals and 24 strategies questionnaire divided into categories, performance indicators of the factors have been measured. Research methods include visits for professionals directly and e-mail survey. In addition, the major developed countries are analyzed by comparing the performance management system. 0.2 or less is absolute importance of performance indicators to evaluate indicators for reconsideration, it is necessary to improve the indicators. Performance indicators as a low priority relative to other indicators of performance indicators for the process as a replacement is needed. The major developed countries through the performance management system can be obtained as follows. Performance management systems should be clearly within the responsibility, independence, and decision-making. Researchers: Eui-Sik Hwang, Joo-Nyung Heo, Kwang-Seok Chae, Yong-Won Cho, and Chang-Ho Kim Research period: 2007. 9. - 2007. 12. E-mail: eshwang@krei.re.kr